Pengaruh Gaji Tunjangan Dan Fasilitas Kerja Terhadap Kinerja Karyawan Pada Karya Sepakat Metro KSO Di Kabupaten Lombok Tengah - Fadila Putri Agnesti; Satriawan (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This study aims to determine (1) the effect of salary on employee performance, (2) the effect of benefits on employee performance, (3) the effect of work facilities on employee performance, (4) the effect of salary, benefits and work facilities on employee performance. In this study using associative research type with a total population and sample of 30 people who are employees at Karya Sepakat Metro Kso in Central Lombok Regency. The data collection technique used in this study was in the form of a statement in the form of a questionnaire. Data analysis techniques used are measuring scales, instrument tests, classical assumption tests, multiple linear analysis, hypothesis testing and the coefficient of determination (R2) using SPSS 25. The results show that: (1) Salary does not significantly affect employee performance because the calculated t value is smaller than t table (0.620 < 2.05553), (2) Benefits are not significant to employee performance because the calculated t calculated value is greater than the t table value (0.650 < 2.05553), (3) Facilities work has a significant effect on employee performance because the calculated t value is greater than t table (2.710 > 2.05553). (4) Salary, Benefits and Work Facilities have a significant effect on employee performance because the F value is greater than F table (14,161 > 2.95).